Kebijakan Pemerintah di Bidang Penanaman Modal Asing (PMA) dalam Rangka Meningkatkan Iklim Investasi di Indonesia (Lex Jurnalica, 2009)
Development at Indonesian by design get new been said is begun since Orde Baru, one that is enlightened deep each Repelita. Development nationaling to constitute exhaustive aware effort nation to lift degree and dignity so on a line with other nations at world. That development performing is alone not only mensyaratkan most actually development authorized capital in savvy most actually natural resourceses, but also given most actually tangible the other capital skill, management ability technology, etc.. On developments early phases, really feels that Indonesian nation ability haven't sufficed to get perform independent ala development. Technological limitation, skill and management ability and financial as serious constraint in development per-forming. To settle that constraint, government invites intern capital to do investment at Indonesian.Keywords: Development, Investment, Regulation